Environmental Protection Due to Reclamation On Bungin Island, West Nusa Tenggara - Chintya Khaerunnisa; Supriyadi; Susianto (Postgraduate University of Merdeka Malang, 2025)
The beach reclamation project undertaken by the Bajo tribe community on Bungin Island, Sumbawa, was carried out voluntarily due to land scarcity caused by high population density. Without a sufficient legal basis and environmental assessment, this activity damages marine ecosystems such as seagrass beds and coral reefs. This research examines the form of legal protection for the environment in reclamation based on the principle of sustainable development, the impact of reclamation, and efforts to enforce environmental law in this case. The method used is empirical legal with a sociological approach thru observation and interviews. The results show that legal protection is not yet effective due to weak supervision, low public legal awareness, and the lack of integration of reclamation with environmental regulations. Although national laws are already in place, local implementation is still weak. This research recommends synergy between the government and the community, increased environmental law literacy, and the development of local regulations based on sustainable development.